Constraining Ministerial Power: The Impact of Veto Players on Labor Market Reforms in Industrial Democracies, 1973-2000 - Becher, Michael (Sage, 2009)
This article investigates how veto players affect the reform of labor market policies in advanced industrial democracies. Complementing Tsebelis’s veto player model with the assumption of ministerial agenda control within the cabinet, the argument is that the constitutional and partisan distribution of veto power affects the capability of ministers to change the status quo in line with their partisan goals. This claim is tested with panel data on unemployment insurance entitlements and employment protection legislation in 20 OECD countries between 1973 and 2000. The central finding is that veto players constrain the power of ministers, cabinet ministers and prime ministers alike, to pursue their partisan interests. The partisanship of ministers shapes reforms only if the ideological distance between veto players is relatively small, and the influence of ministerial partisanship declines as ideological distance increases.
Keywords: ODS 1 - Fin de la pobreza; ODS 8 - Trabajo decente y crecimiento económico; ODS 9 - Industria, innovación e infraestructura; ODS 10 - Reducción de las desigualdades; ODS 16 - Paz, justicia e instituciones sólidas